Proposta de um modelo de protocolo de auditoria do nível de implantação da construção enxuta para a indústria da construção civil - Comelli, Mariana Lira (2017)
The implementation of lean construction in the construction industry generally presents strong barriers that can make it unfeasible, as it happens in the adhesion of other processes of organizational improvements. To correctly guide this process, the use of an efficient audit model in companies that use this philosophy of production management corroborates the effective operation of lean construction. In this sense, the main objective of this work is to propose a model of an audit protocol for the level of implementation of lean construction for the companies that make up the construction industry. To this end, an analysis was made of the literature on the implementation of lean construction and the identification of existing models of evaluation of lean construction, national and international. This review collaborated in the elaboration of a pilot model of audit protocol, which underwent pre-tests in four construction companies, chosen by the degree of representativeness within Fortaleza CE in the use of the philosophy. This stage allowed for the adjustment of the evaluation criteria contained in this model, the mapping of the sources of evidence that prove the fulfillment of these criteria and the identification of opportunities for improvement for the protocol. Subsequently, the protocol was submitted to the analysis of five experts and consolidated after these evaluations. At the end of the research, it was possible to conclude that the evaluation models analyzed do not offer companies the means to verify at what level of implementation the philosophy is found. Also, it was possible to develop an audit protocol model that could be used as a tool to collaborate with companies in the implementation of lean construction as a philosophy of production management.